2023
DOI: 10.1021/acsapm.3c01752
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Multistimulus Response Silicon-Bridged/Fe3O4 Epoxy Vitrimer: Controllable Welding, Crack Healing, and Shape Memory

Mingfeng Chen,
Bing Chen,
Dingsi Li
et al.

Abstract: The emergence of vitrimer materials containing dynamic bonds provides a solution to the dilemma that traditional epoxy resins are difficult to recycle and reuse. However, the development of vitrimer materials with multiple functions, especially simultaneous multistimulus response properties, is still challenging. In this work, Fe 3 O 4 nanoparticle was introduced into epoxy vitrimer (ETOD-SA), containing Si−O segments and dynamic reversible ester bonds, to prepare a multistimulus response silicon-bridged/Fe 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 51 publications
0
1
0
Order By: Relevance
“…This increased healing response demonstrates a synergistic effect from combining both the absorbance of GNPls and the plasmonic resonance effect of the AuNPs. We should note that these ultrafast healing times outperform previous literature. , …”
Section: Results and Discussionmentioning
confidence: 51%
“…This increased healing response demonstrates a synergistic effect from combining both the absorbance of GNPls and the plasmonic resonance effect of the AuNPs. We should note that these ultrafast healing times outperform previous literature. , …”
Section: Results and Discussionmentioning
confidence: 51%
“…These approaches have proved useful in both elastomers and thermosets. , Recently, there has been work on direct silyl ether metathesis using catalysts, Bronsted or Lewis acids, or the introduction of free hydroxyls into the network. , Du Prez and co-workers have developed siloxane-containing vitrimers with very fast dynamics (below 10 s) in the presence of basic catalysts. , Due to the flexibility of the siloxane units, the prepared resins exhibited low viscosities, which offers significant advantages for fiber-reinforced polymer composite manufacturing. Additionally, it has been shown that the incorporation of siloxane groups into reprocessable networks improves the dielectric properties and ductility. , …”
mentioning
confidence: 99%